ANALISIS STRATEGI PEMASARAN GOJEK DALAM MENARIK KONSUMEN DI ERA DIGITAL - Kalisya Khairani Pohan; Margareth Yediza Olivia Hutasoit; Tiara Putri (PT. Saha Kreasi Indonesia, 2025)
This study discusses the marketing strategies used by Gojek to attract consumers in today's digital era. The purpose of this study is to determine how Gojek's marketing strategies are able to compete amid modern technology. The method used in this study is a literature review, collecting various sources such as journals, articles, and Gojek's digital marketing strategies. In today's digital era, Gojek has been shown to utilize social media, digital promotions, and service innovations to increase user appeal and trust. In addition, collaboration strategies with various service companies have also been an important factor in increasing public interest.